Handbook of Epoxy Blends - Parameswaranpillai, Jyotishkumar; Hameed, Nishar; Pionteck, Jürgen; Woo, Eamor M. (Springer International Publishing : Imprint: Springer, 2017)
This reference work compiles and summarizes the available information on epoxy blends. It covers all essential areas - the synthesis, processing, characterization and applications of epoxy blends - in a comprehensive manner. The handbook is highly application-oriented and thus serves as a valuable, authoritative reference guide for researchers, engineers, and technologists working on epoxy blends, but also for graduate and postgraduate students, polymer chemists, and faculties at universities and colleges.The handbook is divided into three parts and organized by the types of blends and components: Part I covers epoxy rubber blends, Part II focuses on epoxy thermoplastic blends, and Part III examines epoxy block-copolymer blends. Each part starts with an introduction, and the individual chapters provide readers with comprehensive information on the synthesis and processing, analysis and characterization, properties and applications of the different epoxy blends. All parts conclude witha critical evaluation of the applications, weighing their advantages and drawbacks. Leading international experts from corporate and academic research institutions and universities discuss the correlations of different epoxy blend properties with their macro-, micro- and nanostructures. This handbook thus offers a rich resource for newcomers to the field, and a major reference work for experienced researchers, the first of its kind available on the market. As epoxies find extremely broad applications, e.g. in oil & gas, in the chemical industry, building and construction industry, automotive, aviation and aerospace, boat building and marine applications, in adhesives and coatings, and many more, this handbook addresses researchers and practitioners from all these fields.